STUDI KARAKTERISTIK PROSES PIROLISIS CEPAT RDF-5 BEBRBAHAN DASAR LIMBAH AREN DAN KOPI DENGAN PENGIKAT LIMBAH PLASTIK TERHADAP KUANTITAS BIO-OIL - Muhammad Riswanda; Herman Saputro; Danar Susilo Wijayanto (Nozel : Jurnal Pendididikan Teknik Mesin, 2023)
Currently, the Indonesian people are faced with various problems in terms of waste management, both organic and inorganic waste. Some of the wastes that can be used are palm waste, coffee grounds and HDPE plastic waste which can be used as alternative fuels, one of which is through the pyrolysis process. Pyrolysis is a process of chemical decomposition of a material thermally in the absence of oxygen. This pyrolysis process converts RDF-5 biomass into a liquid smoke product in the form of bio-oil. This study aims to determine the quantity of pyrolysis oil through the best variation of the composition ratio used. In this study used composition ratio variables, namely 50%:30%:20%, 40%:40%:20%, and 30%:50%:20%. The results of this study obtained the best quantity from a mixture ratio of 50% palm waste, 30% coffee grounds and 20% HDPE plastic to produce 200 ml. The composition ratio affects the quantity of pyrolysis oil results. RDF-5 from palm waste and coffee grounds with HDPE plastic waste binder produces a quantity that tends to decrease as the composition ratio of palm waste waste decreases.